Adolescents' Judgments of Doubly Deviant Peers: Implications of Intergroup and Intragroup Dynamics for Disloyal and Overweight Group Members. Issue 2 (23rd March 2016) - Abrams, Dominic; Palmer, Sally B.; Van de Vyver, Julie; Hayes, Daniel; Delaney, Katrina; Guarella, Sophie; Purewal, Kiran
Abstract: Group membership, loyalty, and weight are highly relevant for adolescent peer evaluations at school. This research tested how in‐group/out‐group membership affected judgments of peers who deviated from social norms for weight and loyalty. Two hundred and forty 11–13‐year‐olds (49 percent female; 94 percent Caucasian) judged two in‐group or out‐group peers: one was normative (loyal and average weight) and the other was non‐normative (i.e., 'deviant'). The deviant target was overweight, disloyal to their own group (school), or both ('doubly deviant'). Derogation of overweight relative to average weight peers was greater if they were in‐group rather than out‐group members, revealing a strong 'black sheep effect' for overweight peers. Disloyal out‐group deviants were judged favorably, but this effect was eliminated if they were doubly deviant, suggesting that their disloyalty was insufficient to overcome the overweight stigma. Consistent with developmental subjective group dynamics theory, effects of group membership and types of deviance on adolescents' favorability toward peers were mediated by adolescents' perceptions of how well the deviant members would 'fit' with the in‐group school. Implications for theory and strategies to reduce peer exclusion, particularly weight stigmatization, are considered.